Perkembangan Pendidikan Formal Pada Masa Pemerintahan Sultan Muhammad Mulia Ibrahim Tsafiudin Di Sambas Kalimantan Barat Tahun (1931 – 1943) - Tarhan, Raden Muhammad; Winarti, Murdiyah (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2023)
This research aims to find out the Islamic education in the era of Sultan Muhammad Mulia Ibrahim Tsafiuddin in 1931-1943, the influences of the Netherlands on the education in Sambas while the government of Sultan Muhammad Mulia Ibrahim Tsafiuddin in 1931-1943, and the system of education Madrasah Al-Sultaniyah. The method of this research is historical research. The descriptive-analytic research methods include four stages: heuristic, verification, interpretation, and historiography. The results of this research show that Islamic education in the era of Sultan Muhammad Mulia Ibrahim Tsafiuddin is the continuation of the education of Madrasah Al-Sultaniyah with the orientation in the education of religion and development to be Tarbiyatul Islam. Islamic education in Sambas gained influences from the Netherlands, and we can see from Tarbiyatul that Islam included all of the studied from Holland Inlandsche School (HIS) in their curriculum. Modern science, especially the Dutch language in Tarbiyatul Islam, is seen as a tool for gaining significant progress. The formal education system in Sambas through Madrasah Al-Sultaniyah or Tarbiyatul Islam combines Islamic education and Dutch education.